Given the equation - x² + 5x = 3, which can be rewritten as:
- x² + 5x - 3 = 0
where a = -1, b = 5 and c = -3.
Quadratic formula:
![\frac{-b\text{ }\pm\text{ }\sqrt[]{b^2\text{ - 4ac}}}{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%5Ctext%7B%20%7D%5Cpm%5Ctext%7B%20%7D%5Csqrt%5B%5D%7Bb%5E2%5Ctext%7B%20-%204ac%7D%7D%7D%7B2a%7D)
Now, we just replace the values of a, b and c on the equation above.
![\frac{-5\text{ }\pm\text{ }\sqrt[]{5^2\text{ - 4(-1)(3)}}}{2(-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B-5%5Ctext%7B%20%7D%5Cpm%5Ctext%7B%20%7D%5Csqrt%5B%5D%7B5%5E2%5Ctext%7B%20-%204%28-1%29%283%29%7D%7D%7D%7B2%28-1%29%7D)
=
Answer:
I will take a look
Step-by-step explanation:
please mark me brainliest here ;)
Answer:
3
Step-by-step explanation:
The natural log is the inverse of the exponential (and vise versa), so ln(e^3) = 3.
(This is the also same as e^(ln3))
Answer:
the angle of elevation of a cloud from a point 60m above a lake is 30 and the angle of depression of the reflection of the cloud in the lake is 60 - Mathematics ... the reflection of the cloud in the lake is 60* find the height of the cloud from the surface of the lake
Step-by-step explanation:
Hope this helps